The dynamics of violations interoception in patients with anorexia nervosa during treatment - A. A. Pichikov; Y. V. Popov; Y. A. Yakovleva; N. I. Ananieva; T. A. Salomatina; L. R. Akhmerova; E. V. Andreev (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
Anorexia nervosa is a disorder, that mostly starts at teenage years. In addition, one of the most important feature of that period is transformation of size and shape of a teenager’s body, that leads to changes in his perception of his own body. Anorexia nervosa is also characterized by tranformation of interoceptive processing, and it is a phenomena which predisposes and maintains eating disorder. We studied the features of interception (accuracy, sensibility, awareness) of girls who suffer anorexia nervosa under therapy and during the catamnesis. Also had been provided study of interoceptive accuracy in stress situation, connected with eating (800 kcal). Significant differences in interoceptive indicators in dynamic between the control group and research group was found.